(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2013)
Tuberculosis (TB) is a chronic granulamatous disorder presenting mostly (80%) as a pulmonary disease, the extra-pulmonary presentation being relatively uncommon. The oral cavity can sometimes be a site for extra-pulmonary tuberculosis with a highly variable clinical presentation including ulceration, diffuse infl ammatory lesions, granulomas and fi ssures. Oral lesions usually appear secondary to a primary tubercular infection elsewhere, although primary infection of the oral mucosa by Mycobacterium tuberculosis has been described. We report here a rare case of primary tuberculosis of the hard palate extending to gingiva, manifesting as gingival enlargement with ulceration. Diagnosis was established by histopathological examination of tissue biopsy and by chest radiography. The patient was put on anti-tubercular therapy for nine months to which a prompt response was obtained. This emphasizes the need to consider tuberculosis in the differential diagnosis of non-healing mucosal lesions of oral cavity for early diagnosis and prompt treatment. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2013; X(1); 37-39 DOI: http://dx.doi.org/10.3126/saarctb.v10i1.8675